Sequence Diversity in Genes of Lipid Metabolism - Garcia, Christine Kim; Mues, Gabriele; Liao, Yuanlan; Hyatt, Tommy; Patil, Nila; Cohen, Jonathan C.; Hobbs, Helen H. (Genome Research, 2001)
Elevated plasma lipoprotein levels play a crucial role in the development of coronary artery disease. Genetic factors strongly influence the levels of plasma lipoproteins, but the genes and sequence variations contributing to the most common forms of dyslipidemias are not known. We used GeneChip probe arrays to resequence the coding regions of 10 key genes of lipid metabolism. The sequences of these genes were analyzed in 80 dyslipidemic individuals. Fourteen nonsynonymous and twenty-two synonymous single nucleotide changes were identified that could be confirmed by conventional sequencing. Seven of the fourteen nonsynonymous sequence variants were polymorphisms with allele frequency >1% in the general population. The remaining seven were not found in normolipidemic controls (25 Caucasians and 25 African-Americans). The relationship between nonsynonymous sequence variations and various dyslipidemias was explored in association and family studies. No evidence was found for coding sequence variations in any of the 10 genes contributing to dyslipidemia. Only a single sequence variation, a missense mutation in the low density lipoprotein receptor gene, co-segregated with hyperlipidemia in the proband's family. This study illustrates some of the difficulties associated with identifying sequence variations contributing to complex traits.
10.1101/gr.172301